2021
DOI: 10.47405/mjssh.v6i3.710
|View full text |Cite
|
Sign up to set email alerts
|

Sikap dan Kesediaan Pelajar Tingkatan Empat Terhadap Perlaksanaan Kemahiran Berfikir Aras Tinggi dalam Pembelajaran Matematik

Abstract: Kajian ini bertujuan untuk meninjau tahap sikap dan kesediaan pelajar Tingkatan Empat terhadap perlaksanaan KBAT dalam pembelajaran matematik. Di samping itu, kajian ini turut melihat sejauh mana perbezaan sikap dan kesediaan pelajar terhadap perlaksanaan KBAT dalam matematik berdasarkan faktor jantina disamping melihat kewujudan hubungan sikap dan kesediaan terhadap perlaksanaan KBAT dengan prestasi matematik pelajar. Seramai 132 orang responden yang terdiri daripada pelajar Tingkatan Empat di sebuah sekolah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…This finding is consistent with the study of Ngah and Zakaria (2016), who found that pupils' attitudes towards HOTS in mathematics problem-solving are moderate. However, these findings differ from the study of Subeli and Rosli (2021), who reported that the level of pupils' Attitude towards HOTS in Mathematics is moderately high. The slight difference in pupils' attitudes can be attributed to the difference in the mean score interpretation used.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This finding is consistent with the study of Ngah and Zakaria (2016), who found that pupils' attitudes towards HOTS in mathematics problem-solving are moderate. However, these findings differ from the study of Subeli and Rosli (2021), who reported that the level of pupils' Attitude towards HOTS in Mathematics is moderately high. The slight difference in pupils' attitudes can be attributed to the difference in the mean score interpretation used.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the findings of Abdullah and Rahman (2020) were consistent with the findings of this study. Despite that, this study contradicts the study of Subeli and Rosli (2021), which reported that the level of readiness of pupils towards HOTS in Mathematics was moderately high. The inconsistency of the findings may be due to the difference in the readiness measures.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations